1997
DOI: 10.1074/jbc.272.18.12100
|View full text |Cite
|
Sign up to set email alerts
|

pch1 +, a Second Essential C-type Cyclin Gene in Schizosaccharomyces pombe

Abstract: The Schizosaccharomyces pombe gene pch1 ؉ (pombe cyclin C homology) was isolated in a two-hybrid screen for proteins that interact with Cdc2. The cyclin box region of Pch1 protein shares greatest sequence identity with mammalian and Drosophila C-type cyclins (ϳ33% identity). Pch1 is significantly less similar to Mcs2 (19% identity), a second member of the C-type cyclin family in S. pombe. Cdc2 co-precipitates with Pch1 in S. pombe cell lysates, although Cdc2 may not be the major catalytic partner of a Pch1 kin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
14
0
1

Year Published

1998
1998
2007
2007

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 56 publications
0
14
0
1
Order By: Relevance
“…This high degree of similarity is also shared with an S. cerevisiae cyclin C homolog, Srb11 (32). Pch1 is an essential C-type cyclin whose function is unknown (21). SRB11 mutants were identified as suppressors of the Cs phenotype of partial truncation mutants in CTD (58), and alleles of SRB11 have been isolated in three other screens for mutations involved in the regulated repression of transcription (ssn8, are1, and ume1 mutants).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This high degree of similarity is also shared with an S. cerevisiae cyclin C homolog, Srb11 (32). Pch1 is an essential C-type cyclin whose function is unknown (21). SRB11 mutants were identified as suppressors of the Cs phenotype of partial truncation mutants in CTD (58), and alleles of SRB11 have been isolated in three other screens for mutations involved in the regulated repression of transcription (ssn8, are1, and ume1 mutants).…”
Section: Resultsmentioning
confidence: 99%
“…CTK2, a C-type cyclin, and CTKK1, a CTD kinase, form a complex in vivo, although a role in transcription has not been demonstrated (55). In addition, several related cyclin-Cdk complexes have been identified in S. pombe, but their roles in transcription or Cdk activation are unknown (4,11,21,36).…”
mentioning
confidence: 99%
“…Since then, cyclins with significant homology to the cyclin box region of cyclin C have also been found in Schizosaccharomyces pombe (14,39). Except for a recent study carried out in murine cells (36), there has been no evidence supporting a critical role for C-type cyclins in cell cycle progression.…”
mentioning
confidence: 92%
“…pombe extracts showed that the cyclin was associated with a CTD kinase activity (23); however, the identity of the catalytic subunit was not established. Given that the Bur1/Bur2 complex is important for transcription in S. cerevisiae and that it phosphorylates the pol II CTD (18, 24), we can tentatively impute similar activities to SpCdk9/Pch1.…”
Section: Mutations Of the Kinase Active Site And T-loop Abolish Spcdkmentioning
confidence: 99%